First record of Roederiodes Coquillett (Diptera: Empididae: Clinocerinae) from South America, with description of a new species from Colombia, and key to males of species south of the United States of America - Ramos-Pastrana, Yardany; Córdoba-Suarez, Eric; Sinclair, Bradley J. (Zootaxa, 2026)
Among Empididae, the genus Roederiodes is easily recognizable by its narrow wings, broad gena and narrow, elongated proboscis. Currently, 13 species are recognized in the New World, distributed from Canada to Costa Rica. This is the first record of Roederiodes in South America. Roederiodes primus sp. nov. is described from Colombia (type locality: Parque Natural Regional Cerro Páramo de Miraflores, Garzón, Huila). Illustrations and an updated key and distribution map are presented.